PERSEPSI GURU PADA SOAL OPEN ENDED - Nurhasanah Nurhasanah (Fitrah, 2022)
The ability to think creatively which is the goal of K13 is one of the desired skills in the world of work so it must be instilled while still in school because creativity determines human resources to improve human welfare. Creative thinking requires convergent and divergent thinking, problem finding and problem solving and is closely related to open-ended thinking. This study aims to determine the teacher's perception of open ended questions. The subjects of this study were four SMK mathematics teachers. The approach used is a qualitative approach. The results of this study were that there were two teachers who had developed and used open-ended questions and two teachers had never developed and used open-ended questions. The main obstacle for teachers who have developed is the difficulty in finding topics that are meaningful and easy to develop. The obstacle for teachers who have never developed is that teachers do not believe in students because students still have difficulty working on easy questions and teachers still have low interest in the development and use of open ended questions.